2021
DOI: 10.31814/stce.nuce2021-15(2)-10
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of axial strength in circular steel tube confined concrete columns using artificial intelligence

Abstract: In recent years, together with the boom of the industrial revolution 4.0, terms such as artificial intelligence (AI) are gradually gaining popularity engineering domain. This study proposed a number of AI models for predicting the axial strength in circular steel tube confined concrete (STCC) columns. Particularly, artificial neural networks (ANNs), support vector regression (SVR), linear regression (LR), and M5P were applied in this study. This study applied 136 samples of short and intermediate STCC columns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the testing phase, the proposed model showed acceptable accuracy with a mean absolute percentage error of 11.10%. Ngo et al [29] used artificial neural networks (ANNs), support vector regression (SVR), linear regression (LR), and M5P techniques for the prediction of axial strength in circular steel tube confined concrete columns. The authors outlined key distinctions between the techniques and concluded that the M5P was the best artificial intelligence (AI) model for predicting experimental results when compared to others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the testing phase, the proposed model showed acceptable accuracy with a mean absolute percentage error of 11.10%. Ngo et al [29] used artificial neural networks (ANNs), support vector regression (SVR), linear regression (LR), and M5P techniques for the prediction of axial strength in circular steel tube confined concrete columns. The authors outlined key distinctions between the techniques and concluded that the M5P was the best artificial intelligence (AI) model for predicting experimental results when compared to others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, ANN outperforms the other three models while also showing high regression values. Ngo et al . (2021) performed the performance analysis of four models on short to intermediate circular CFST columns.…”
Section: Techniques Used To Predict the Acc Of Cfst Columnsmentioning
confidence: 99%